(untitled) (Bangladesh Journal of Public Administration, 2022)
In Bangladesh, women’s engagement in economic activities in general and in agriculture in a particular area has remained low, but in modern times, the participation of women in agriculture has rapidly increased and also contributed to economic activities according to the survey guided by the Bureau of Statistics. Women’s role is changing from unpaid family workers to farm managers, a phenomenon termed as “feminization of agriculture” in absence of males. In order to determine the involvement of women in agricultural activities, secondary data from a representative sample survey in 62 villages conducted by the Bangladesh Bureau of Statistics from 2000 to 2022 was used in conjunction with primary data from the Bangladeshi districts of Dinajpur, Cumilla, and Moulvibazar. The results show that 71% of women engaged in agricultural activities in 2022, an increase of about 11% from 2000. The participation was restricted to mostly crop farming, livestock and poultry rearing which is a marginal economic activity with the allocation of only about 1.5 hours of labor per day. Only 22% of the female workers participated in crop farming in 2022, compared to 45% of men. Only about 5% of the women participated in the agricultural labor market in 2000 and 2022. Women’s participation in the agricultural labor market remains insignificant at 3.07% of agricultural workers. A regression analysis shows that women’s engagement in agriculture is negatively related to land holding, different age gap, education of household members and wage rate, on the other hand, favorable way with the women’s ages, the number of their homes that are irrigated, their membership in NGOs, the village’s isolation, and the wage rate for agriculture in the community.